Optimization on effects of design parameter on displacement amplification ratio of 2 DOF working platform employing Bridge-type compliant mechanism flexure hinge using Taguchi method. (August 2019) - Wang, Chia Nan; Truong, Kim Phung; Huynh, Ngoc Thai; Nguyen, Ho
Abstract: High precision positioning systems was usually utilized in industrial applications. But the systems have workspace limits. Therefore, a new design for 2-DOF working platform employing two bride-type compliant mechanism flexure hinge was suggested in this paper. The INVENTOR 2018 software was used to design the mechanism and the output displacement, output stress were obtained by Finite element method in ANSYS. The simulation results were achieved maximum value for output displacement of 0.61 mm according x axis direction and y direction, and maximum value for output stress of 120 MPa while input displacement of 0.01 mm, input body length of 5 mm, fillet of radius of 0.2 mm, incline angle of 1.2 degree, width of flexure hinge of 2 mm, thickness of flexure hinge changes from 0.25 mm to 0.75 mm. The simulation results of two remain cases was also presented and discussed. In three cases, thickness of flexure hinge has important effected on output displacement and output stress. The maximum value of displacement amplification ratio was achieved 61.13 by simulation for two x and y axis directions. The S/N analysis demonstrated the design parameters have important effects on output displacement and stress. The optimal total displacement amplification ratio was obtained 91.35 compared with the predicted value of 98.08 that was good agree with 6.86% deviation error and the optimal value of stress was obtained 73.3562 MPa compared with the predicted value of 80.0936 MPa that was good agree with deviation error 8.41%.